Synthesis, Structural Characterization, Electrochemical and Antimicrobial Studies of Complexes from the NO Ligating Schiff Bases of Furoic Acid Hydrazide - M.A, Hapipah; M. Zain, Sharifuddin; Jefrey B, Wan; S.M, Rahuma; Rohaiza S.O, harifah; Abdullah, Noorlidah; H.L, Teoh (Malaysian Journal of Science, 2004)
Some new cobalt(II) and manganese(II) complexes with Schiff base derived from the condensation of 2-hydroxyacetophenone (L1), 5-chloro-2-hydroxyacetophenone (L2), thiophene-2¬carboxaldehyde (L3), 3-methylthiophene-2-carboxaldehyde (L4) and 2,4-dihydroxybenzaldehyde (L5), with furoic acid hydrazide have been prepared. Another two cobalt complexes with Shiff bases obtained from 2-hydroxyacetophenone (L6), 5-chloro-2-hydroxyacetophenone (L7) with 2-hydroxy-2¬naphtholichydrazide were also synthesized. All the complexes were characterized by means of FTIR, FT H-NMR, C-NMR, elemental analyses, electrochemical studies, thermogravimetric analysis. From FTIR and H-NMR data, complexation of the ligand occurs in the enolic/ketonic forms via the azomethine nitrogen and the carbonyl oxygen. In contrast, the 2-hydroxy-2-naphtholic hydrazide Schiff base coordinates to cobalt through keto form only. The electrochemical oxidation and reduction of the complexes have been studied by using cyclic voltammetry. The complexes showed varied antibacterial activity against the bacteria tested while showing less inhibition against the fungi tested.Some new cobalt(II) and manganese(II) complexes with Schiff base derived from the condensation of 2-hydroxyacetophenone (L1), 5-chloro-2-hydroxyacetophenone (L2), thiophene-2¬carboxaldehyde (L3), 3-methylthiophene-2-carboxaldehyde (L4) and 2,4-dihydroxybenzaldehyde (L5), with furoic acid hydrazide have been prepared. Another two cobalt complexes with Shiff bases obtained from 2-hydroxyacetophenone (L6), 5-chloro-2-hydroxyacetophenone (L7) with 2-hydroxy-2¬naphtholichydrazide were also synthesized. All the complexes were characterized by means of FTIR, FT H-NMR, C-NMR, elemental analyses, electrochemical studies, thermogravimetric analysis. From FTIR and H-NMR data, complexation of the ligand occurs in the enolic/ketonic forms via the azomethine nitrogen and the carbonyl oxygen. In contrast, the 2-hydroxy-2-naphtholic hydrazide Schiff base coordinates to cobalt through keto form only. The electrochemical oxidation and reduction of the complexes have been studied by using cyclic voltammetry. The complexes showed varied antibacterial activity against the bacteria tested while showing less inhibition against the fungi tested.Some new cobalt(II) and manganese(II) complexes with Schiff base derived from the condensation of 2-hydroxyacetophenone (L1), 5-chloro-2-hydroxyacetophenone (L2), thiophene-2¬carboxaldehyde (L3), 3-methylthiophene-2-carboxaldehyde (L4) and 2,4-dihydroxybenzaldehyde (L5), with furoic acid hydrazide have been prepared. Another two cobalt complexes with Shiff bases obtained from 2-hydroxyacetophenone (L6), 5-chloro-2-hydroxyacetophenone (L7) with 2-hydroxy-2¬naphtholichydrazide were also synthesized. All the complexes were characterized by means of FTIR, FT H-NMR, C-NMR, elemental analyses, electrochemical studies, thermogravimetric analysis. From FTIR and H-NMR data, complexation of the ligand occurs in the enolic/ketonic forms via the azomethine nitrogen and the carbonyl oxygen. In contrast, the 2-hydroxy-2-naphtholic hydrazide Schiff base coordinates to cobalt through keto form only. The electrochemical oxidation and reduction of the complexes have been studied by using cyclic voltammetry. The complexes showed varied antibacterial activity against the bacteria tested while showing less inhibition against the fungi tested.